Impact of adopting maize hermetic storage technologies on smallholder farmers’ income in Gatsibo District, Rwanda - Benimana, Gilberthe Uwera; Ritho, Cecilia; Irungu, Patrick (Elsevier, 2023)
Rapid population growth has increased the global demand for food. However, some studies have revealed that more than one-third of the global food production is lost during postharvest operations along the food supply chain. Managerial and technical limitations such as a lack of proper storage facilities, poor handling practices and, associated knowledge are among the main causes of food losses particularly in Africa. Maize is among the most important staple food and cash crops across sub-Saharan Africa. In Rwanda, most of the maize produced incurs losses during storage. Hermetic storage technologies (HST) have been proven to be effective in the control of post-harvest storage losses in maize. However, their adoption in maize storage has been low with farmers continuing to use less effective technologies. Therefore, this study assessed the impact of hermetic maize storage technologies adoption, on the income of 301 randomly selected smallholder maize farmers in Gatsibo District of Rwanda, using the endogenous switching regression (ESR). The results revealed that household size, post-harvest training, access to credit, distance to input provider, and the household head's experience in maize production were the major factors influencing farmers' decision to adopt HST. The occupation of the household head, number of plots reserved for other crops, training, household size, age of the household head, and household maize self-sufficiency goal significantly influenced income for both HST adopters and non-adopters. Overall, the adoption of HST had a positive and significant impact on income from stored maize, among those who adopted it. The study recommends that the government of Rwanda and other stakeholders should support the dissemination of HST to facilitate access. Thus, increased access to institutional support services such as post-harvest training, credit access, and agricultural input supply, should be a major part of efforts aimed at promoting the effective use of hermetic maize storage technologies among smallholder maize farmers in Rwanda.